2008
DOI: 10.1007/s10096-008-0532-4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of plasmid-mediated AmpC β-lactamases among clinical isolates of Escherichia coli and Klebsiella pneumoniae from five children’s hospitals in China

Abstract: The purpose of this study was to investigate the prevalence of plasmid-mediated AmpC beta-lactamases in Escherichia coli and Klebsiella pneumoniae from five children's hospitals in China. A total of 494 E. coli and 637 K. pneumoniae isolates were collected from five children's hospitals in China from 2005 to 2006. The isolates with decreased susceptibility to cefoxitin were subjected to confirmation test with 3-aminophenyl boronic acid. Polymerase chain reaction (PCR) amplification of the blaAmpC, blaTEM, blaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
26
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 27 publications
8
26
0
3
Order By: Relevance
“…These strains were amplified with full-length primer encoding a fragment of 1,140 bp, and the PCR products obtained were purified, sequenced and identified as being the DHA-1 type. The positive rate of pAmpC β-lactamase-producing Klebsiella pneumoniae in the samples from Xuzhou tertiary hospitals was 10.8%, which was consistent with the report by Ding et al (29), but higher than the rate reported by Alvarez et al (30). Although CMY is the most common type of AmpC β-lactamase in the world, the DHA-1 and ACT types predominate in China (31).…”
supporting
confidence: 87%
“…These strains were amplified with full-length primer encoding a fragment of 1,140 bp, and the PCR products obtained were purified, sequenced and identified as being the DHA-1 type. The positive rate of pAmpC β-lactamase-producing Klebsiella pneumoniae in the samples from Xuzhou tertiary hospitals was 10.8%, which was consistent with the report by Ding et al (29), but higher than the rate reported by Alvarez et al (30). Although CMY is the most common type of AmpC β-lactamase in the world, the DHA-1 and ACT types predominate in China (31).…”
supporting
confidence: 87%
“…In addition, chromosomal Ambler class C AmpC genes have been mobilized and are now being disseminated on plasmids, reminiscent of the early dissemination and evolution of ESBLs (11). Increasingly, reports document the detection of plasmid-mediated AmpC resistance (pAmpC) in E. coli (4,6,12). Data from the SENTRY antimicrobial surveillance program for North America show that 19/65 ESBL screen-positive E. coli isolates harbored pAmpC (5).…”
mentioning
confidence: 99%
“…In addition, chromosomal Ambler class C AmpC genes have been mobilized and are now being disseminated on plasmids, reminiscent of the early dissemination and evolution of ESBLs (21). Increasingly, reports document the detection of plasmid-mediated AmpC ␤-lactamase (pAmpC) resistance in the Enterobacteriaceae (7,9,22). Data from the SENTRY Antimicrobial Surveillance Program for North America show that 19 of 65 ESBL screen-positive E. coli isolates harbored pAmpC (8).…”
mentioning
confidence: 99%